Identification of a CD11b(+)/Gr-1(+)/CD31(+) myeloid progenitor capable of activating or suppressing CD8(+) T cells - Bronte, Vincenzo (2000)
Apoptotic death of CD8(+) T cells can be induced by a population of inhibitory myeloid cells that are double positive for the CD11b and Gr-1 markers. These cells are responsible for the immunosuppression observed in pathologies as dissimilar as tumor growth and overwhelming infections, or after immunization with viruses. The appearance of a CD11b(+)/Gr-1(+) population of inhibitory macrophages (i Macs) could be attributed to high levels of granulocyte-macrophage colony-stimulating factor (GM-CSF) in vivo. Deletion of i Macs in vitro or in vivo reversed the depression of CD8(+) T-cell function. We isolated i Macs from the spleens of immunocompromised mice and found that these cells were positive for CD31, ER-MP20 (Ly-6C), and ER-MP58, markers characteristic of granulocyte/monocyte precursors. Importantly, although i Macs retained their inhibitory properties when cultured in vitro in standard medium, suppressive functions could be modulated by cytokine exposure. Whereas culture with the cytokine interleukin 4 (IL-4) increased i Mac inhibitory activity, these cells could be differentiated into a nonadherent population of fully mature and highly activated dendritic cells when cultured in the presence of IL-4 and GM-CSF. A common CD31(+)/CD11b(+)/Gr-1(+) progenitor can thus give rise to cells capable of either activating or inhibiting the function of CD8(+) T lymphocytes, depending on the cytokine milieu that prevails during antigen-presenting cell maturation.